2006
DOI: 10.1111/j.1538-7836.2006.01789.x
|View full text |Cite
|
Sign up to set email alerts
|

P2Y12 receptor‐mediated potentiation of thrombin‐induced thromboxane A2 generation in platelets occurs through regulation of Erk1/2 activation

Abstract: Summary. Background: Thromboxane A 2 (TXA 2 ) is a positive feedback lipid mediator that is generated upon stimulation of platelets with various agonists. Aspirin works as an antithrombotic drug by blocking the generation of TXA 2 . The aim of this study was to evaluate the role of the purinergic P2Y receptors in thrombin-induced TXA 2 generation. Results: PAR1-activating peptide (SFLLRN), PAR4-activating peptide (AYPGKF), and thrombin, induced the activation of cytosolic phospholipase A 2 (cPLA 2 ), release o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(119 citation statements)
references
References 48 publications
5
111
0
1
Order By: Relevance
“…Recent studies showed an additional antiplatelet activity via the AA-TBXA2-COX pathway potentiating the effects of ASA, which implies that cessation of clopidogrel affects both, the ADP-and AA-induced platelet aggregation (55,(150)(151)(152)(153) contributing to the rebound effect.…”
Section: Platelets Inflammation and Antiinflammatory Drugs In Acs Anmentioning
confidence: 99%
“…Recent studies showed an additional antiplatelet activity via the AA-TBXA2-COX pathway potentiating the effects of ASA, which implies that cessation of clopidogrel affects both, the ADP-and AA-induced platelet aggregation (55,(150)(151)(152)(153) contributing to the rebound effect.…”
Section: Platelets Inflammation and Antiinflammatory Drugs In Acs Anmentioning
confidence: 99%
“…[18][19][20] It is well-established that P2Y 12 blockade has significant effects upon platelet responsiveness to collagen, U46619, and PAR4 agonists consistent with its antithrombotic effect in man. [21][22][23] We found that the P2Y 12 receptor blocker PAM (3 mM) markedly prevented agonist-induced single platelet loss as compared with vehicle (0.5% DMSO). This inhibition persisted even at the highest concentrations tested of collagen (72 6 10% vs 58 6 11%), PAR4-amide (80 6 4% vs 11 6 6%), and U46619 (50 6 15% vs 1 6 1%) ( Figure 3A-C).…”
Section: Detection Of the Antiplatelet Effect Of P2y 12 Receptor Blocmentioning
confidence: 73%
“…As we also examined platelet reactivity using ASPI test and platelet count and did not find significant differences between the examined groups, we assumed that platelet aggregation differences are specifically due to the strategy of clopidogrel cessation. However, previous data suggested that there is an interaction between clopidogrel and the arachidonic acid-induced pathway of platelet reactivity [11][12][13][14]. Sambu et al [14] reported finding that when clopidogrel is withdrawn one year after DES implantation, there is a significant increase in AA-induced platelet reactivity in addition to an increase in ADP-induced platelet reactivity.…”
Section: Primary Endpointmentioning
confidence: 99%